Fine-grained copper-nickel-tin alloy for suppressing d03 structure transformation and method for manufacturing the same
Patent Information
- Application Number
- CN202611188208.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-09
AI Technical Summary
[0007]针对相关技术的不足,本发明提供了一种抑制D03结构转变的细晶铜镍锡合金及其制备方法,具备制备兼具高强度和优异塑性铜镍锡合金的优点,解决了Cu-Ni-Sn-Al合金中Al加速纳米析出相析出但易向有害D03结构转变、破坏延伸率的问题
(1)本发明通过Al、Re与低温短时固溶工艺三重协同作用,具体为:Al加速纳米γ'相析出以提升强度,Re抑制γ'相向有害D03结构的过快转变以保护塑性,低温短时固溶细化晶粒以提供细晶强化,协同实现合金在获得高强度的同时保持良好的延伸率,解决了含Al的Cu-Ni-Sn合金析出速率与组织稳定性之间的矛盾。
Smart Images

Figure CN122879546A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a fine-grained copper-nickel-tin alloy that suppresses the DO3 structural transformation and its preparation method, belonging to the technical field of high-performance copper alloy materials. Background Technology
[0002] High-strength, high-elasticity copper alloys are widely used in aerospace, electronics, and precision instruments. While beryllium copper alloys offer excellent performance, they contain the highly toxic element beryllium, which is harmful to human health and the environment. Furthermore, they suffer from severe stress relaxation at high temperatures, limiting their applications. Therefore, developing safe, non-toxic, high-temperature resistant, and high-performance beryllium copper alloys has become an urgent industry need.
[0003] Cu-Ni-Sn age-hardened copper alloys are considered one of the most promising alternatives to beryllium copper due to their high strength, high elasticity, non-toxicity, and low cost. These alloys achieve excellent mechanical properties by inducing amplitude modulation decomposition through aging treatment to form a coherent γ'-(Cu,Ni)3Sn strengthening phase with the matrix. However, conventional Cu-Ni-Sn alloys have a slow aging response, typically requiring 8–12 hours to reach peak aging, resulting in long production cycles and high energy consumption, which limits their large-scale application.
[0004] To accelerate the aging precipitation process of Cu-Ni-Sn alloys, various microalloying strategies have been explored. Studies have shown that Co alloying can enhance the unstable decomposition of Cu-Ni-Co-Si alloys, promote the formation of the GP zone (Ginniel-Preston zone), and significantly shorten the incubation period of precipitates. The addition of trace amounts of Co and P elements has a regulatory effect on the amplitude-modulated decomposition and discontinuous precipitation reaction of Cu-15Ni-8Sn alloys. The addition of Si has also attracted attention; the addition of 0.15% Si to Cu-9.5Ni-2.3Sn alloys can induce the precipitation of new Ni2Si and Ni3Si phases, thereby further strengthening the alloy. However, the above studies mostly focus on the effects of adding a single element and fail to solve the fundamental contradiction between the aging precipitation rate and the microstructure stability. Although Co and Si elements can accelerate precipitation, they can introduce new evolution paths for precipitates, leading to microstructure instability.
[0005] To address the aforementioned issues, Al can promote the formation of Sn-rich solute atom clusters in the early stages of aging, significantly accelerating the amplitude-modulated decomposition process and serving as an effective way to accelerate the precipitation of nanoscale γ' strengthening phases. However, the accelerating effect of Al easily leads to the excessively rapid precipitation of the γ' phase, which readily bypasses the metastable stage and rapidly transforms into the equilibrium DO3 structure (i.e., the γ-DO3 phase). The γ-DO3 phase loses its coherent relationship with the copper matrix, becoming a coarse, incoherent equilibrium phase that typically forms along grain boundaries and severely degrades the mechanical properties of the alloy, especially significantly impairing elongation. This invention addresses the problem of excessively rapid γ' phase precipitation by adding trace amounts of Re (rhenium) to the Cu-Ni-Sn-Al alloy. Re has an extremely high melting point and extremely low solubility in the copper matrix, tending to segregate at grain boundaries. Furthermore, the segregation of Re at grain boundaries effectively hinders the short-range diffusion of solute atoms near the grain boundaries, thereby suppressing the rapid transformation of the γ' phase to the DO3 structure. This allows the γ' phase to maintain a metastable structure coherent with the matrix for a longer period, continuously providing a strengthening effect without compromising plasticity. Currently, there is no research on using Re to suppress the transformation of the γ' phase to the DO3 structure in Cu-Ni-Sn alloys. In addition, solution treatment of Cu-Ni-Sn alloys is usually carried out at temperatures above 900℃ for 1-2 hours to ensure sufficient dissolution of alloying elements. However, high-temperature, long-duration solution treatment leads to rapid grain coarsening, severely impairing the alloy's plasticity and toughness. Under the premise of achieving sufficient solute atom dissolution, lowering the solution temperature and shortening the holding time can significantly refine the grain structure and further improve the overall mechanical properties of the alloy through grain refinement strengthening.
[0006] Cu-Ni-Sn alloys, as the most promising beryllium copper alternatives, have broad application prospects in aerospace, electronics, and precision instruments. However, while Al-containing Cu-Ni-Sn alloys can accelerate the precipitation of the nano-γ' phase, they face the dilemma of deteriorated elongation due to the transformation of the γ' phase to the DO3 structure, and the grain coarsening caused by high-temperature long-term solid solution further exacerbates the loss of plasticity. This invention achieves this by synergistically combining Al-accelerated precipitation, Re-inhibition of the DO3 transformation, and low-temperature short-time solid solution to refine grains. While leveraging the advantage of Al-accelerated nano-γ' phase precipitation, it utilizes Re to effectively suppress the excessively rapid transformation of the γ' phase to the DO3 structure, and refines grains through low-temperature short-time solid solution and inhibits recrystallization grain growth, thereby obtaining a fine-grained copper-nickel-tin alloy with both high strength and excellent plasticity, which can meet the high-performance requirements of elastic components. Summary of the Invention
[0007] To address the shortcomings of related technologies, this invention provides a fine-grained copper-nickel-tin alloy that suppresses the transformation of DO3 structure and its preparation method. It has the advantages of preparing copper-nickel-tin alloys with both high strength and excellent ductility, and solves the problem in Cu-Ni-Sn-Al alloys where Al accelerates the precipitation of nano-precipitates but easily transforms into harmful DO3 structures, thus compromising elongation.
[0008] One of the objectives of this invention is to provide a fine-grained copper-nickel-tin alloy that suppresses the DO3 structural transformation. The raw material composition of the alloy, by mass percentage, includes: 7-11% Ni, 4-8% Sn, 0.1-0.9% Al, 0.05-0.5% Re, with the balance being copper and unavoidable impurities.
[0009] Preferably, the raw materials for the alloy are weighed in a Ni to Sn mass ratio of (0.9~2.8):1.
[0010] More preferably, Ni and Sn in the raw materials of the alloy are weighed in a mass ratio of (1.3~1.8):1.
[0011] Preferably, the raw materials for the alloy are weighed in a Re to Al mass ratio of (0.06~5):1.
[0012] More preferably, the raw materials for the alloy are weighed in a Re to Al mass ratio of (0.3~0.6):1.
[0013] The second objective of this invention is to provide a method for preparing a fine-grained copper-nickel-tin alloy that suppresses the DO3 structural transformation, specifically including the following steps: (1) Billet casting: Weigh out pure metals Cu, Ni, Sn, Al and Ni-Re intermediate alloy raw materials in proportion, mix the raw materials and melt and heat them, and then cast them to obtain alloy ingots.
[0014] (2) Homogenization: The alloy ingot is homogenized and then surface impurities and oxide layer are removed to obtain homogenized alloy billet.
[0015] (3) Deformation process: The homogenized alloy billet is subjected to hot rolling deformation and cold rolling deformation treatment in sequence to obtain alloy plate.
[0016] (4) Low-temperature short-time solution treatment: The alloy plate is subjected to low-temperature short-time solution treatment to obtain the alloy plate after solution treatment.
[0017] (5) Aging treatment: The alloy plate after solution treatment is subjected to aging treatment to obtain a fine-grained copper-nickel-tin alloy that suppresses the transformation of DO3 structure.
[0018] Preferably, the Ni-Re master alloy in step (1) comprises 10% Re by mass percentage, with the balance being Ni.
[0019] Preferably, the melting in step (1) is carried out in an inert atmosphere (such as argon); the melting temperature is 1350~1400℃; and the heat preservation condition is: heat preservation at 1350~1400℃ for 10~20min.
[0020] More preferably, the melting in step (1) is carried out in a vacuum induction melting furnace (such as a vacuum medium-frequency induction furnace).
[0021] More preferably, the heat preservation conditions in step (1) are: heat preservation at 1400℃ for 15 minutes.
[0022] More preferably, the purity of the pure metal raw material in step (1) is ≥99.9%.
[0023] Preferably, the homogenization process in step (2) is carried out at 880-920℃ for 6-12 hours.
[0024] More preferably, the homogenization treatment in step (2) is carried out at 880~920℃ for 12 hours.
[0025] Preferably, the conditions for hot rolling deformation treatment in step (3) are: each pass is held at 830~850℃ for 10~15 minutes before rolling, the total number of hot rolling deformation treatments is 8~15, and the total deformation amount of hot rolling deformation treatment is 50~60%; the conditions for cold rolling deformation treatment are: the total number of cold rolling deformation treatments is 10~15, and the total deformation amount of cold rolling deformation treatment is 70~90%.
[0026] More preferably, the cold rolling deformation treatment in step (3) is carried out at room temperature.
[0027] More preferably, the total number of passes for hot rolling deformation treatment in step (3) is 10; the total number of passes for cold rolling deformation treatment is 10.
[0028] Preferably, the conditions for the low-temperature short-time solution treatment in step (4) are: heat treatment at 600~700℃ for 0.5h, followed by water quenching.
[0029] Preferably, the aging treatment in step (5) is performed by holding the temperature at 350-450℃ for 4-8 hours, followed by cooling with the furnace.
[0030] More preferably, the cooling method in step (5) is air cooling.
[0031] Mechanism of the invention: This invention simultaneously adds trace amounts of Al and Re elements to a Cu-Ni-Sn alloy and employs low-temperature, short-time solid solution treatment to achieve a synergistic strengthening effect. The fine-grained copper-nickel-tin alloy prepared by this invention achieves accelerated precipitation of nano-precipitates, promotes the formation of Sn-rich solute atom clusters in the early stages of aging, significantly accelerates the amplitude-modulated decomposition process, and promotes the uniform precipitation of nano-scale γ'-(Cu,Ni)3Sn strengthening phase, thereby greatly improving the alloy's strength and shortening the aging peak time, providing an excellent strength foundation for the alloy. Furthermore, due to the synergistic effect of the added Al and Re elements, this invention achieves the suppression of the excessively rapid transformation of the γ' phase to the harmful DO3 structure. Re atoms tend to agglomerate at grain boundaries, producing a pinning effect on the grain boundaries. The agglomeration of Re at grain boundaries can effectively hinder the short-range diffusion of solute atoms near the grain boundaries, thereby suppressing the excessively rapid transformation of the γ' phase to the equilibrium DO3 structure. Reducing the number of nucleation sites and lowering the free energy difference can effectively suppress the formation of the γ-DO3 phase. The addition of Re achieves effective suppression of the DO3 transformation by occupying grain boundary nucleation sites and changing the diffusion dynamics near the grain boundaries, enabling the γ' phase to maintain a metastable structure coherent with the matrix for a longer period of time, continuously providing a strengthening effect without impairing plasticity. This invention employs a triple synergistic effect of Al, Re, and a low-temperature, short-time solution process to refine the grains of the prepared copper-nickel-tin alloy and effectively suppress the growth of recrystallized grains and abnormal grain growth. The low-temperature, short-time solution process maintains a fine and uniform grain structure, providing a significant grain refinement strengthening effect. Simultaneously, the low-temperature solution process causes some CuNi2Sn phases to fail to completely remelt and remain at the grain boundaries. These unremelted second phases, together with Re, pin the grain boundaries, further suppressing recrystallized grain growth. Furthermore, the low-temperature solution process partially preserves the substructures and dislocation networks generated by cold deformation. These substructures provide numerous heterogeneous nucleation sites for subsequent aging precipitation, further promoting the uniform precipitation of nanoscale strengthening phases.
[0032] This invention achieves a triple synergy of Al, Re, and low-temperature short-time solid solution process. Each component works synergistically and is indispensable. The synergy of the three achieves multiple benefits of fine grain strengthening, precipitation strengthening, and microstructure stabilization. Ultimately, a microstructure with small grain size, uniform and dispersed γ' strengthening phase, and no D03 transformation is formed, thus enabling the alloy to obtain excellent strength, elasticity, and plasticity matching.
[0033] The beneficial effects of this invention are: (1) This invention achieves a triple synergistic effect of Al, Re and low-temperature short-time solid solution process, specifically: Al accelerates the precipitation of nano γ' phase to improve strength, Re inhibits the excessively rapid transformation of γ' phase to harmful DO3 structure to protect plasticity, and low-temperature short-time solid solution refines grains to provide fine grain strengthening. The synergistic effect enables the alloy to achieve high strength while maintaining good elongation, thus solving the contradiction between precipitation rate and microstructure stability of Al-containing Cu-Ni-Sn alloy.
[0034] (2) By adding trace amounts of Re, the present invention effectively suppresses the rapid transformation of the γ' phase to the DO3 structure by utilizing the segregation effect of Re at the grain boundary, forming an acceleration-inhibition synergistic mechanism with Al, thus balancing the precipitation rate and the structure stability.
[0035] (3) The present invention adopts a low temperature short-time solid solution process (600~700℃, 0.5h), which effectively refines the grain structure of the alloy (grain size ≤8μm) and effectively inhibits the growth of recrystallized grains, thus realizing the synergistic effect of fine grain strengthening and precipitation strengthening.
[0036] (4) The fine-grained copper-nickel-tin alloy prepared by the present invention has an average grain size of ≤8μm, excellent tensile strength and elongation, and its comprehensive performance is better than that of traditional Cu-Ni-Sn alloys. It can be comparable to or even surpass some beryllium copper alloys. Moreover, the preparation process is safe and non-toxic, simple and inexpensive. Attached Figure Description
[0037] Figure 1 The figures show the engineering stress-strain curves of the copper-nickel-tin alloys prepared in Example 1 and Comparative Example 1 of this invention.
[0038] Figure 2 This is a microstructure diagram of the fine-grained copper-nickel-tin alloy prepared in Example 2 of the present invention.
[0039] Figure 3 The image shows the X-ray diffraction pattern of the fine-grained copper-nickel-tin alloy prepared in Example 3 of this invention.
[0040] Figure 4 This is a microstructure diagram of the fine-grained copper-nickel-tin alloy prepared in Comparative Example 3 of the present invention. Detailed Implementation
[0041] To better illustrate the purpose, technical solution, and advantages of this invention, the invention will be further described below with reference to specific embodiments. In the embodiments and comparative examples of this invention, unless otherwise specified, all chemical reagents used were commercially available analytical grade reagents. The purity of the pure metal raw materials used in the embodiments and comparative examples of this invention is ≥99.9%. The vacuum melting method used in this invention is a conventional technique in the art for melting copper alloys, and its purpose is to utilize a vacuum environment to melt alloy raw materials and obtain alloy ingots. To achieve effective degassing and protection, the vacuum level in the furnace is evacuated to a conventional range; the determination of this specific value is a conventional operation in the art.
[0042] The raw material composition (in mass percentage, %) of each embodiment and comparative example of the present invention is shown in Table 1.
[0043] Example 1 A method for preparing a fine-grained copper-nickel-tin alloy that suppresses the D03 structural transformation specifically includes the following steps: (1) Casting of billet: Weigh copper blocks, nickel granules, tin balls, aluminum granules and Ni-Re master alloy (which includes 10% Re by mass percentage and the balance Ni) according to the proportions shown in Table 1. Use acetone to ultrasonically clean the oil stains on the surface of the raw materials, use sandpaper to polish the surface oxide layer, then use anhydrous ethanol to ultrasonically clean the impurities and dry them. Mix the treated raw materials and put them into a vacuum medium frequency induction furnace. Use high-purity argon to clean the furnace twice and melt it under vacuum conditions. The melting temperature is 1350~1400℃ and the melting atmosphere is high-purity argon. After the raw materials are completely melted, stabilize the current and keep it at 1400℃ for 15 minutes. Then pour it into a preheated mold to obtain an alloy ingot.
[0044] (2) Homogenization: The alloy ingot is placed in a muffle furnace and homogenized at 880°C for 12 hours. Then it is cooled by water quenching and the surface impurities and oxide layer are removed to obtain the homogenized alloy billet.
[0045] (3) Deformation process: The homogenized alloy billet is heated to 830°C and held for 10 minutes. It is then subjected to 10 passes of hot rolling deformation treatment, with a total deformation of 60%. After hot rolling, it is subjected to 10 passes of cold rolling deformation treatment at room temperature, with a total deformation of 80%, to obtain the alloy plate.
[0046] (4) Low temperature short-time solution treatment: Heat the alloy plate to 600℃, keep it at that temperature for 0.5h, and then quickly quench it in water to room temperature to obtain the alloy plate after solution treatment.
[0047] (5) Aging treatment: The alloy plate after solution treatment is heated to 450°C and held for 4 hours, and then air-cooled to room temperature to obtain a fine-grained copper-nickel-tin alloy that suppresses the transformation of DO3 structure.
[0048] The mechanical properties of the fine-grained copper-nickel-tin alloy obtained in this embodiment were tested. The results showed that the ultimate tensile strength of the alloy was 952 MPa, the yield strength was 694 MPa, and the elongation was approximately 21.2%. (See [link to relevant documentation]). Figure 1 .
[0049] Scanning electron microscopy (SEM) analysis was performed on the fine-grained copper-nickel-tin alloy prepared in this embodiment. The results showed that the alloy prepared in this embodiment had uniform and fine grain size, with an average grain size of approximately 5.5 μm. X-ray diffraction analysis of the alloy revealed that it consisted of an α-Cu matrix and a CuNi2Sn second phase. No harmful DO3 structure diffraction peaks were detected, indicating that the addition of Re effectively suppressed the transformation of the γ' phase to the DO3 structure.
[0050] Example 2 A method for preparing a fine-grained copper-nickel-tin alloy that suppresses the D03 structural transformation specifically includes the following steps: (1) Casting of billet: Weigh copper blocks, nickel granules, tin balls, aluminum granules and Ni-Re master alloy (which includes 10% Re by mass percentage and the balance Ni) according to the proportions shown in Table 1. Use acetone to ultrasonically clean the oil stains on the surface of the raw materials, use sandpaper to polish the surface oxide layer, then use anhydrous ethanol to ultrasonically clean the impurities and dry them. Mix the treated raw materials and put them into a vacuum medium frequency induction furnace. Use high-purity argon to clean the furnace twice and melt it under vacuum conditions. The melting temperature is 1350~1400℃ and the melting atmosphere is high-purity argon. After the raw materials are completely melted, stabilize the current and keep it at 1400℃ for 15 minutes. Then pour it into a preheated mold to obtain an alloy ingot.
[0051] (2) Homogenization: The alloy ingot is placed in a muffle furnace and homogenized at 900°C for 12 hours. Then it is cooled by water quenching and the surface impurities and oxide layer are removed to obtain the homogenized alloy billet.
[0052] (3) Deformation process: The homogenized alloy billet is heated to 840℃ and held for 13 minutes. It is then subjected to 10 passes of hot rolling deformation treatment, with a total deformation of 60%. After hot rolling, it is subjected to 10 passes of cold rolling deformation treatment at room temperature, with a total deformation of 80%, to obtain the alloy plate.
[0053] (4) Low temperature short-time solution treatment: Heat the alloy plate to 650°C, hold for 0.5h, and then quickly quench it in water to room temperature to obtain the alloy plate after solution treatment.
[0054] (5) Aging treatment: The alloy plate after solution treatment is heated to 400°C and held for 6 hours, and then air-cooled to room temperature to obtain a fine-grained copper-nickel-tin alloy that suppresses the transformation of DO3 structure.
[0055] The mechanical properties of the fine-grained copper-nickel-tin alloy obtained in this embodiment were tested. The results showed that the ultimate tensile strength of the fine-grained copper-nickel-tin alloy prepared in this embodiment was 915 MPa, the yield strength was 656 MPa, and the elongation was about 25.5%.
[0056] The fine-grained copper-nickel-tin alloy prepared in this embodiment was analyzed by scanning electron microscopy, such as... Figure 2 As shown in the figure. The results indicate that the alloy prepared in this embodiment has a uniform and fine grain size, with an average grain size of approximately 6.5 μm. In this embodiment, the alloy formed a uniform and fine equiaxed grain structure through the synergistic effect of low-temperature short-time solid solution process and Al and Re microalloying. X-ray diffraction analysis of the alloy showed that it consists of an α-Cu matrix and a CuNi2Sn second phase, and no D03 structure diffraction peaks were detected.
[0057] Example 3 A method for preparing a fine-grained copper-nickel-tin alloy that suppresses the D03 structural transformation specifically includes the following steps: (1) Casting of billet: Weigh copper blocks, nickel granules, tin balls, aluminum granules and Ni-Re master alloy (which includes 10% Re by mass percentage and the balance Ni) according to the proportions shown in Table 1. Use acetone to ultrasonically clean the oil stains on the surface of the raw materials, use sandpaper to polish the surface oxide layer, then use anhydrous ethanol to ultrasonically clean the impurities and dry them. Mix the treated raw materials and put them into a vacuum medium frequency induction furnace. Use high-purity argon to clean the furnace twice and melt it under vacuum conditions. The melting temperature is 1350~1400℃ and the melting atmosphere is high-purity argon. After the raw materials are completely melted, stabilize the current and keep it at 1400℃ for 15 minutes. Then pour it into a preheated mold to obtain an alloy ingot.
[0058] (2) Homogenization: The alloy ingot is placed in a muffle furnace and homogenized at 920°C for 12 hours. Then it is cooled by water quenching and the surface impurities and oxide layer are removed to obtain the homogenized alloy billet.
[0059] (3) Deformation process: The homogenized alloy billet is heated to 850℃ and held for 10 minutes. It is then subjected to 10 passes of hot rolling deformation treatment, with a total deformation of 50%. After hot rolling, it is subjected to 10 passes of cold rolling deformation treatment at room temperature, with a total deformation of 90%, to obtain the alloy plate.
[0060] (4) Low temperature short-time solution treatment: Heat the alloy plate to 700℃, hold for 0.5h, and then quickly quench it in water to room temperature to obtain the alloy plate after solution treatment.
[0061] (5) Aging treatment: The alloy plate after solution treatment is heated to 350°C and held for 8 hours, and then air-cooled to room temperature to obtain a fine-grained copper-nickel-tin alloy that suppresses the transformation of DO3 structure.
[0062] The mechanical properties of the fine-grained copper-nickel-tin alloy obtained in this embodiment were tested. The results showed that the ultimate tensile strength of the fine-grained copper-nickel-tin alloy prepared in this embodiment was 1038 MPa, the yield strength was 775 MPa, and the elongation was about 18.4%.
[0063] Scanning electron microscopy (SEM) analysis of the fine-grained copper-nickel-tin alloy prepared in this embodiment showed that the alloy had uniform and fine grain size, with an average grain size of approximately 5.7 μm. X-ray diffraction analysis of the alloy yielded the following results: Figure 3As shown in the diagram, the diffraction peaks of the face-centered cubic (FCC) copper-based solid solution (i.e., α-Cu) are present in the XRD patterns, along with diffraction peaks of the CuNi2Sn second phase. This second phase is a Sn-rich phase that remains at the grain boundaries after solution treatment because it did not completely remelt into the copper matrix. Due to the use of low-temperature, short-time solution treatment, the solution temperature is lower than that of conventional Cu-Ni-Sn alloys, resulting in some CuNi2Sn phase not fully remelting and remaining at the grain boundaries. No characteristic diffraction peaks of the DO3 structure were detected in the XRD patterns, indicating that the addition of Re effectively suppressed the transformation of the γ' phase into the harmful DO3 structure.
[0064] Comparative Example 1 This comparative example uses the same method as Example 1 to prepare the alloy material, the only difference being that Al and Re raw materials were not added in this comparative example (i.e., the basic Cu-9Ni-6Sn alloy). The specific steps include: (1) Casting of billet: Weigh copper blocks, nickel granules and tin balls according to the proportions shown in Table 1. Use acetone to ultrasonically clean the oil stains on the surface of the raw materials, use sandpaper to polish the surface oxide layer, then use anhydrous ethanol to ultrasonically clean the impurities and dry them. Mix the treated raw materials and put them into a vacuum medium frequency induction furnace. Use high-purity argon to clean the furnace twice and melt it under vacuum conditions. The melting temperature is 1350~1400℃ and the melting atmosphere is high-purity argon. After the raw materials are completely melted, stabilize the current and keep it at 1400℃ for 15 minutes. Then pour it into a preheated mold to obtain an alloy ingot.
[0065] (2) Homogenization: The alloy ingot is placed in a muffle furnace and homogenized at 880°C for 12 hours. Then it is cooled by water quenching and the surface impurities and oxide layer are removed to obtain the homogenized alloy billet.
[0066] (3) Deformation process: The homogenized alloy billet is heated to 830°C and held for 10 minutes. It is then subjected to 10 passes of hot rolling deformation treatment, with a total deformation of 60%. After hot rolling, it is subjected to 10 passes of cold rolling deformation treatment at room temperature, with a total deformation of 80%, to obtain the alloy plate.
[0067] (4) Low temperature short-time solution treatment: Heat the alloy plate to 600℃, keep it at that temperature for 0.5h, and then quickly quench it in water to room temperature to obtain the alloy plate after solution treatment.
[0068] (5) Aging treatment: The alloy plate after solution treatment is heated to 450°C and held for 4 hours, and then air-cooled to room temperature to obtain copper-nickel-tin alloy.
[0069] The mechanical properties of the copper-nickel-tin alloy prepared in this comparative example were tested. The results showed that the ultimate tensile strength of the copper-nickel-tin alloy prepared in this comparative example was 576 MPa, the yield strength was 391 MPa, and the elongation was approximately 42.6%. (See [reference needed]). Figure 1 The comparative alloy was subjected to low-temperature short-time solid solution treatment, and the average grain size was about 12.8 μm. However, due to the lack of Al and Re, the aging precipitation strengthening effect was not good. X-ray diffraction analysis of the alloy showed that it was composed of an α-Cu matrix and a CuNi2Sn second phase.
[0070] Comparative Example 2 This comparative example uses the same method as Example 2 to prepare the alloy material, the only difference being that Re raw material (i.e., Cu-7Ni-4Sn-0.1Al alloy) was not added in this comparative example. The specific steps include: (1) Casting of billet: Weigh copper blocks, nickel granules, tin balls and aluminum granules according to the proportions shown in Table 1. Use acetone to ultrasonically clean the oil stains on the surface of the raw materials, use sandpaper to polish the surface oxide layer, then use anhydrous ethanol to ultrasonically clean the impurities and dry them. Mix the treated raw materials and put them into a vacuum medium frequency induction furnace. Use high-purity argon to clean the furnace three times and melt it under vacuum conditions. The melting temperature is 1300~1350℃ (the melting temperature of the raw materials in this comparative example is lower because Re is not added). The melting atmosphere is high-purity argon. After the raw materials are completely melted, stabilize the current and keep it at 1350℃ for 15 minutes. Then pour it into a preheated mold to obtain an alloy ingot.
[0071] (2) Homogenization: The alloy ingot is placed in a muffle furnace and homogenized at 900°C for 12 hours. Then it is cooled by water quenching and the surface impurities and oxide layer are removed to obtain the homogenized alloy billet.
[0072] (3) Deformation process: The homogenized alloy billet is heated to 840℃ and held for 13 minutes. It is then subjected to 10 passes of hot rolling deformation treatment, with a total deformation of 60%. After hot rolling, it is subjected to 10 passes of cold rolling deformation treatment at room temperature, with a total deformation of 80%, to obtain the alloy plate.
[0073] (4) Low temperature short-time solution treatment: Heat the alloy plate to 650°C, hold for 0.5h, and then quickly quench it in water to room temperature to obtain the alloy plate after solution treatment.
[0074] (5) Aging treatment: The alloy plate after solution treatment is heated to 400°C and held for 6 hours, and then air-cooled to room temperature to obtain copper-nickel-tin alloy.
[0075] Mechanical properties of the copper-nickel-tin alloy prepared in this comparative example were tested. The results showed that the ultimate tensile strength of the copper-nickel-tin alloy prepared in this comparative example was 836 MPa, the yield strength was 664 MPa, and the elongation was approximately 9.7%. The average grain size of the alloy in this comparative example was approximately 12.1 μm. This alloy was treated with low-temperature short-time solid solution treatment, and Al was added but Re was not added. Due to the lack of Re's inhibitory effect on the DO3 transformation, the γ' phase rapidly transformed into the harmful DO3 structure during aging. X-ray diffraction analysis of the alloy showed that it consisted of an α-Cu matrix and a CuNi2Sn second phase, and characteristic diffraction peaks of the DO3 structure were detected, confirming that the formation of the harmful DO3 phase was the main reason for the severe deterioration of the elongation.
[0076] Comparative Example 3 This comparative example uses the same method as Example 1 to prepare the alloy material, the only difference being that this comparative example uses a high-temperature long-time solution treatment instead of a low-temperature short-time solution treatment, specifically including the following steps: (1) Casting of billet: Weigh copper blocks, nickel granules, tin balls, aluminum granules and Ni-Re master alloy (which includes 10% Re by mass percentage and the balance Ni) according to the proportions shown in Table 1. Use acetone to ultrasonically clean the oil stains on the surface of the raw materials, use sandpaper to polish the surface oxide layer, then use anhydrous ethanol to ultrasonically clean the impurities and dry them. Mix the treated raw materials and put them into a vacuum medium frequency induction furnace. Use high-purity argon to clean the furnace twice and melt it under vacuum conditions. The melting temperature is 1350~1400℃ and the melting atmosphere is high-purity argon. After the raw materials are completely melted, stabilize the current and keep it at 1400℃ for 15 minutes. Then pour it into a preheated mold to obtain an alloy ingot.
[0077] (2) Homogenization: The alloy ingot is placed in a muffle furnace and homogenized at 880°C for 12 hours. Then it is cooled by water quenching and the surface impurities and oxide layer are removed to obtain the homogenized alloy billet.
[0078] (3) Deformation process: The homogenized alloy billet is heated to 830°C and held for 10 minutes. It is then subjected to 10 passes of hot rolling deformation treatment, with a total deformation of 60%. After hot rolling, it is subjected to 10 passes of cold rolling deformation treatment at room temperature, with a total deformation of 80%, to obtain the alloy plate.
[0079] (4) High temperature and long time solution treatment: Heat the alloy plate to 920°C, keep it at that temperature for 2 hours, and then quickly quench it in water to room temperature to obtain the alloy plate after solution treatment.
[0080] (5) Aging treatment: The alloy plate after solution treatment is heated to 450°C and held for 4 hours, and then air-cooled to room temperature to obtain copper-nickel-tin alloy.
[0081] The mechanical properties of the copper-nickel-tin alloy prepared in this comparative example were tested. The results showed that the ultimate tensile strength of the copper-nickel-tin alloy prepared in this comparative example was 873 MPa, the yield strength was 734 MPa, and the elongation was approximately 2.9%. Scanning electron microscopy analysis of the copper-nickel-tin alloy prepared in this comparative example yielded the following results: Figure 4 As shown. This comparative alloy, due to the use of high-temperature, long-term solid solution treatment, exhibits significant grain coarsening. Figure 4 The average grain size was found to be approximately 107 μm. Although the composition was exactly the same as in Example 1, with identical Al and Re contents, the coarse grain structure caused the fine-grain strengthening effect to disappear, and the coarse grain structure itself had an adverse effect on plasticity. X-ray diffraction analysis of the alloy revealed that it contained only an α-Cu matrix.
[0082] Comparing Comparative Example 1 and Example 1, both employed low-temperature short-time solution treatment. Comparative Example 1 was a basic Cu-9Ni-6Sn alloy without Al and Re, with a tensile strength of only 592 MPa. In Example 1, the addition of 0.3% Al and 0.1% Re increased the tensile strength to 952 MPa, an increase of 60.8%. With identical solution and aging processes, the significant increase in strength was attributed to Al accelerating the precipitation of the nanoscale γ' strengthening phase, while the addition of Re effectively inhibited the transformation of the γ' phase into the harmful DO3 structure. The two synergistically produced a superimposed effect of precipitation strengthening and microstructure stabilization.
[0083] Comparing Comparative Example 2 and Example 2, both contain 0.1% Al and undergo low-temperature short-time solution treatment. However, Comparative Example 2, without the addition of Re, has a tensile strength of 836 MPa and an elongation of only 9.7%. Example 2, with the addition of 0.05% Re, shows an increase in tensile strength to 915 MPa and a significant increase in elongation to 25.5%. Since both examples have the same Al content and identical solution and aging processes, their aging precipitation strengthening effects are essentially equivalent. In Comparative Example 2, without the addition of Re, the γ' phase rapidly transforms into the harmful DO3 structure during aging, leading to a severe deterioration in elongation. In Example 2, the addition of Re effectively suppresses the rapid transformation of the γ' phase into the DO3 structure, maintaining the γ' phase as a metastable structure coherent with the matrix, and significantly increasing the elongation from 9.7% to 25.5%. XRD analysis also confirms that characteristic diffraction peaks of the DO3 structure were detected in Comparative Example 2, but not in Example 2. This fully demonstrates the irreplaceable role of Re in suppressing the harmful DO3 structure transformation and protecting the alloy's plasticity.
[0084] Comparing Comparative Example 3 and Example 1, both have identical compositions. However, Comparative Example 3 employed a high-temperature, long-duration solution treatment (920℃ / 2h). This high-temperature treatment significantly reduced the segregation of Re at grain boundaries, weakening its inhibitory effect on the D03 transformation. Simultaneously, the high temperature caused a sharp coarsening of the grains (approximately 107 μm), eliminating the grain refinement strengthening effect and drastically reducing the elongation to 2.9%. The tensile strength of the two examples differed by 79 MPa, and the elongation differed by more than seven times. This performance difference is mainly attributed to the significant difference in grain size: the fine-grained structure enhances strength through a grain refinement strengthening mechanism while providing greater grain boundary coordination deformation capability, thus maintaining good plasticity; while the coarse-grained structure simultaneously loses both the grain refinement strengthening effect and plastic deformation capability. This fully demonstrates the irreplaceable nature of the low-temperature, short-duration solution treatment process used in this invention in refining grains and achieving a balance between grain refinement strengthening and plasticity.
[0085] In summary, the embodiments of this invention achieve excellent plasticity while maintaining high strength through the synergistic effect of Al accelerating the precipitation of the nano-γ' phase, Re suppressing the DO3 transformation, and low-temperature short-time solid solution refining the grains. Comparative Example 1 demonstrates the necessity of Al accelerating precipitation; Comparative Example 2 demonstrates the indispensability of Re in suppressing the DO3 transformation, as the lack of Re leads to the transformation of the γ' phase into the harmful DO3 structure and a severe deterioration in elongation; Comparative Example 3 demonstrates the significant advantages of the low-temperature short-time solid solution process compared to the high-temperature long-time solid solution process. Re is added in the form of a Ni-Re master alloy, which allows for precise batching and simple operation, making it suitable for industrial production.
[0086] The various embodiments of the present invention have been described above. These descriptions are exemplary and not exhaustive, nor are they limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments. The terminology used herein is chosen to best explain the principles, practical application, or improvement of the technology in the market, or to enable others skilled in the art to understand the embodiments disclosed herein.
Claims
1. A fine-grained copper-nickel-tin alloy for suppressing the DO3 structural transformation, characterized in that, The raw material composition of the alloy, by mass percentage, includes: 7-11% Ni, 4-8% Sn, 0.1-0.9% Al, 0.05-0.5% Re, with the balance being copper and unavoidable impurities.
2. The fine-grained copper-nickel-tin alloy for suppressing the DO3 structural transformation according to claim 1, characterized in that, The raw materials for the alloy are weighed in a ratio of Ni to Sn of (0.9~2.8):
1.
3. The fine-grained copper-nickel-tin alloy for suppressing the DO3 structural transformation according to claim 1, characterized in that, The raw materials for the alloy are weighed in a Re to Al mass ratio of (0.06~5):
1.
4. The method for preparing a fine-grained copper-nickel-tin alloy that suppresses the DO3 structural transformation as described in any one of claims 1 to 3, characterized in that, Specifically, the following steps are included: (1) Billet casting: Weigh out pure metals Cu, Ni, Sn, Al and Ni-Re intermediate alloy raw materials in proportion, mix the raw materials and melt and heat them, and then cast them to obtain alloy ingots. (2) Homogenization: The alloy ingot is homogenized, and then surface impurities and oxide layers are removed to obtain homogenized alloy billet; (3) Deformation process: The homogenized alloy billet is subjected to hot rolling deformation and cold rolling deformation treatment in sequence to obtain alloy plate; (4) Low-temperature short-time solution treatment: The alloy plate is subjected to low-temperature short-time solution treatment to obtain the alloy plate after solution treatment; (5) Aging treatment: The alloy plate after solution treatment is subjected to aging treatment to obtain a fine-grained copper-nickel-tin alloy that suppresses the transformation of DO3 structure.
5. The method for preparing a fine-grained copper-nickel-tin alloy to suppress the DO3 structural transformation according to claim 4, characterized in that, The step (1) Ni-Re master alloy comprises 10% Re by mass percentage, with the balance being Ni.
6. The method for preparing a fine-grained copper-nickel-tin alloy to suppress the D03 structural transformation according to claim 4, characterized in that, The melting in step (1) is carried out under an inert atmosphere; the melting temperature is 1350~1400℃; the heat preservation condition is: heat preservation at 1350~1400℃ for 10~20min.
7. The method for preparing a fine-grained copper-nickel-tin alloy to suppress the DO3 structural transformation according to claim 4, characterized in that, The conditions for homogenization in step (2) are: heat treatment at 880~920℃ for 6~12h.
8. The method for preparing a fine-grained copper-nickel-tin alloy to suppress the DO3 structural transformation according to claim 4, characterized in that, The conditions for hot rolling deformation treatment in step (3) are as follows: each pass is held at 830~850℃ for 10~15 minutes before rolling, the total number of hot rolling deformation treatments is 8~15, and the total deformation amount of hot rolling deformation treatment is 50~60%; the conditions for cold rolling deformation treatment are as follows: the total number of cold rolling deformation treatments is 10~15, and the total deformation amount of cold rolling deformation treatment is 70~90%.
9. The method for preparing a fine-grained copper-nickel-tin alloy to suppress the D03 structural transformation according to claim 4, characterized in that, The conditions for the low-temperature short-time solution treatment in step (4) are: heat treatment at 600~700℃ for 0.5h, followed by water quenching.
10. The method for preparing a fine-grained copper-nickel-tin alloy to suppress the DO3 structural transformation according to claim 4, characterized in that, The conditions for the aging treatment in step (5) are: heat preservation at 350~450℃ for 4~8h, followed by furnace cooling.